A Prospective Comparative Study of Tacrolimus and Corticosteroids in the Treatment of Atopic Dermatitis - R, Ranjeth; M.S, Amritha; Vijayasenan, Resmi; Wesley, I. John (Journal of Pharmacy Practice and Community Medicine)
Background: Atopic dermatitis is a chronic inflammatory disease which can recur at adulthood particularly in people with genetic predisposition like asthma or other hypersensitivities. It has an adverse impact on the daily life of patients and hence, it is clear that appropriate treatment is necessary; hence the study was carried out to evaluate the efficacy of topical agents Tacrolimus and Corticosteroids. Materials and Methods: This Prospective Observational Study was carried out in 108 patients recruited from the Department of Dermatology, Cosmopolitan Hospital, Thiruvananthapuram for a period of 6 months. A written informed consent was taken. Out of the 108 patients, 54 patients received Topical Tacrolimus and the remaining 54 patients received Topical Corticosteroids. Eczema Area Severity Index (EASI) score analysis was performed at base line and after 2 weeks of drug therapy. Results: The result of the study was developed by comparing EASI scores of all the patients. Two statistical methods were used for developing the result. Independent ‘t’ test for Between Group comparison and Paired ‘t’ test for Within Group comparison. From the statistical evidences, it is deduced that both the drugs are effective for treatment of atopic dermatitis (P - value < 0.05). After comparing both the drugs, it was found that Corticosteroids are more effective than Tacrolimus (P - value < 0.05). Conclusion: From this study, it has been concluded that both the drugs Tacrolimus and Corticosteroids have a significant role in treatment of atopic dermatitis. But on comparison of both the agents, Corticosteroids are found to be more efficacious than Tacrolimus.
Keywords: Atopic Dermatitis; EASI; Tacrolimus; Corticosteroids; Independent ‘t’ test; Paired ‘t’ test.